Expression of ido Gene in Fetal Liver Mesenchymal Stem Cells Following Cryopreservation - Goltsev, Anatoliy N.; Dimitrov, Aleksey Yu.; Gayevskaya, Yuliya A.; Dubrava, Tatyana G.; Babenko, Natalia N.; Lutsenko, Elena D.; Ostankov, Maksim V. (Problems of Cryobiology and Cryomedicine, 2014)
The study was conducted to assess the effect of gestation term and cryopreservation factors on some functional parameters of mesenchymal stem cells (MSCs) in fetal liver (FL), in particular, ido gene expression rate. Expression rate of ido gene was decreased between 14th to 18th days of FL gestation. Following cryopreservation the expression rate of ido gene in FL cells of 18th gestation day increased significantly, and this level exceeded significantly the one in non-frozen samples of the 14th and 18th gestation day. This fact emphasizes the ability of cryopreservation to implement the ‘revitalizing’ effect in respect of FL cells of late gestation terms. Thus, cryopreservation can be used as the method of specific enhancing of MSCs immune modulating activity. Probl Cryobiol Cryomed 2014; 24(1):16–27.